The Strategic Management of Teachers’ Spiritual Competence in Preventing Moral Degradation in Schools - Syaqina, Dianita Widya; Yohamintin, Yohamintin (Journal of Educational Management Research, 2025)
This study aims to determine the importance of teachers' spiritual competence in preventing moral degradation in students. This research used a qualitative method with a case study approach. The data collection techniques in this research were observation, interviews, and documentation. Research data analysis using the interactive model of Miles and Huberman, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that spiritual competence is very important, especially in the context of education because it acts as the main foundation in shaping the character and personality of students who believe and fear God Almighty. Indicators of teacher spiritual competence are (1) Perseverance. Forms of patience and consistency in facing challenges when guiding students. (2) Honesty, an educator who must have a high attitude of honesty and can provide examples and apply honest behavior. (3) Gratitude, an educator must have high sincerity in carrying out his professional duties. (4) Fairness, an educator who is required to be fair to all students.